Histopathological Evaluation of Soybean (Glycine max (L.) Merr.) Strains Resistance to Sclerotium rolfsii Disease - Samiyarsih, Siti; Erlina, Chindy Ayu; Muljowati, Juni Safitri; Fitrianto, Nur (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
Sclerotinia infection of stem and leaf of soybean Glycine max (L.) Merr. caused by the fungal pathogen of Sclerotium rolfsii has recently become more important in the Indonesian soybean production area. This study aimed to evaluate the level of resistance and intensity of infection by S. rolfsii in four soybean strains. The research was arranged in a factorial completely randomized design. The observed variables include the anatomy characteristics of leaves and stems of soybean and disease intensity caused by S. rolfsii. The data were analyzed quantitatively with the Analysis of Variance (ANOVA) at 95% and 99% confidence level, followed by the Least Significant Difference Test (Fisher’s LSD) at the level of 5%. Soybean leaves and stem anatomy inoculated by S. rolfsii showed a decrease in the stomatal density, epidermis thickness, and mesophyll thickness as well as a damaged cuticle, damaged stem epidermis, and swollen stem cortex. Four strains inoculated by S. rolfsii showed a higher disease intensity of 40%-80% compared to the resistant cultivar ('Dering') and susceptible cultivar ('Wilis'), showing disease intensity of 20% and 40%, respectively.